FOUNDATIONS OF VISUAL ARTS AND ART THERAPY IN EDUCATIONAL PRACTICE - Rakhmatova Ikbolkhon Inomjonovna; Ergasheva Go‘zal Ro‘zimurod qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article explores the theoretical foundations and practical significance of visual arts and art therapy within the educational process. The study focuses on the role of visual arts as a means of emotional expression and psychological support, as well as the pedagogical potential of art therapy in fostering students’ emotional well-being, creativity, and personal development. The paper analyzes the historical development of art therapy, its psychological and pedagogical principles, and its integration into visual arts education. Particular attention is given to the therapeutic functions of artistic activity, including emotional regulation, self-awareness, stress reduction, and social adaptation. The findings indicate that the systematic application of art therapy methods in visual arts education enhances both the educational effectiveness and the psychological resilience of learners.